Preclinical Research of Dihydromyricetin for Brain Aging and Neurodegenerative Diseases - Martínez-Coria, Hilda; Mendoza-Rojas, Martha X.; Arrieta-Cruz, Isabel; López-Valdés, Héctor E. (Frontiers in Pharmacology, 2019)
Brain aging and neurodegenerative diseases share the hallmarks of slow and progressive loss of neuronal cells. Flavonoids, a subgroup of polyphenols, are broadly present in food and beverage and numerous studies have suggested that it could be useful for preventing or treating neurodegenerative diseases in humans. Dihydromyricetin [DHM] is one of the main flavonoids of some Asian medicinal plants that are used to treat diverse illness. The effects of DHM have been studied in different in vitro systems of oxidative damage and neuroinflammation, as well as in animal models of several neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease and Huntington’s disease. Here we analyzed the most important effects of DHM, including its antioxidant, anti-inflammatory and neuroprotective effects, as well as its ability to restore GABA neurotransmission and improve motor and cognitive behavior. We propose new areas of research that might contribute to a better understanding of the mechanism of action of this flavonoid, which could help develop a new therapy for aging and age-related brain diseases.